2014
DOI: 10.1590/s1984-29612014043
|View full text |Cite
|
Sign up to set email alerts
|

Amblyomma auricularium (Acari: Ixodidae): underwater survival of the non-parasitic phase of feeding females

Abstract: To determine the effects of immersion in water on the biological parameters of engorged females of the tick species Amblyomma auricularium, 60 females were distributed in six groups, each comprising 10 individuals. The control group -G1 (not immersed) was fixed dorsally in a Petri dish and incubated at 27 ± 1 °C and 80% RH. The other groups were subjected to immersion periods of 24, 48, 72 and 96 hours, and the sixth group to continuous immersion. After the immersion period, the females were placed in Petri di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Much evidence indicates that ticks can survive submersion in fresh water, for extended periods of up to 15 d (although reports also exist of survival underwater for several months; MacLeod 1935; Murray and Vestjens 1967;Smith 1973;Paula et al 2000;Carroll 2003;Louzada and Daemon 2003;Barrett et al 2009;Fielden et al 2011;Giannelli et al 2012;Müeller 2012;Sá-Hungaro et al 2014). We found that little penguin ticks are also capable of surviving for at least 48 h submerged in seawater.…”
Section: Ticks On the Body Surfacementioning
confidence: 47%
See 1 more Smart Citation
“…Much evidence indicates that ticks can survive submersion in fresh water, for extended periods of up to 15 d (although reports also exist of survival underwater for several months; MacLeod 1935; Murray and Vestjens 1967;Smith 1973;Paula et al 2000;Carroll 2003;Louzada and Daemon 2003;Barrett et al 2009;Fielden et al 2011;Giannelli et al 2012;Müeller 2012;Sá-Hungaro et al 2014). We found that little penguin ticks are also capable of surviving for at least 48 h submerged in seawater.…”
Section: Ticks On the Body Surfacementioning
confidence: 47%
“…10% that of spiders and some insects; Lighton and Fielden 1995) and can survive longer than any other arthropod without food or water (Needham and Teel 1991;Lighton and Fielden 1995). Finally, a growing body of evidence suggests that ticks are capable of surviving in fresh water for days to weeks, depending on the species (Murray and Vestjens 1967;Fielden et al 2011;Giannelli et al 2012;Sá-Hungaro et al 2014). Whether these characteristics might enable ticks to survive at sea and regularly at depth has not been explored, although some morphological assessments have suggested that the latter is unlikely (Pugh 1997).…”
Section: Introductionmentioning
confidence: 99%
“…sculptum ticks, which prefer drained soils in open areas with shrubs and riparian forests [ 98 ]. In the laboratory, engorged females from Amblyomma auricularium were resistant to water stress when placed under immersion in distilled water for up to 96 hours [ 99 ]. However, the reduced progeny and the delayed oviposition time were attributed to diapause.…”
Section: Discussionmentioning
confidence: 99%
“…This would be possible if the diapause capability of A. mixtum is activated at times of the year when their survival is threatened. In laboratory [96] found that engorged females from A. auricularium are resistant to water stress, when placed under immersion in distilled water for up to 96 hours, but the reduced progeny and the delayed oviposition time were attributed to diapause.…”
Section: Discussionmentioning
confidence: 99%